Genome analysis of Desulfotomaculum kuznetsovii strain 17T reveals a physiological similarity with Pelotomaculum thermopropionicum strain SIT. Issue 1 (January 2013) - Visser, Michael; Worm, Petra; Muyzer, Gerard; Pereira, Inês; Schaap, Peter; Plugge, Caroline; Kuever, Jan; Parshina, Sofiya; Nazina, Tamara; Ivanova, Anna; Bernier-Latmani, Rizlan; Goodwin, Lynne; et al.
Abstract Desulfotomaculum kuznetsovii is a moderately thermophilic member of the polyphyletic spore-forming genusDesulfotomaculum in the familyPeptococcaceae . This species is of interest because it originates from deep subsurface thermal mineral water at a depth of about 3, 000 m.D. kuznetsovii is a rather versatile bacterium as it can grow with a large variety of organic substrates, including short-chain and long-chain fatty acids, which are degraded completely to carbon dioxide coupled to the reduction of sulfate. It can grow methylotrophically with methanol and sulfate and autotrophically with H2 + CO2 and sulfate. For growth it does not require any vitamins. Here, we describe the features ofD. kuznetsovii together with the genome sequence and annotation. The chromosome has 3, 601, 386 bp organized in one contig. A total of 3, 567 candidate protein-encoding genes and 58 RNA genes were identified. Genes of the acetyl-CoA pathway, possibly involved in heterotrophic growth with acetate and methanol, and in CO2 fixation during autotrophic growth are present. Genomic comparison revealed thatD. kuznetsovii shows a high similarity withPelotomaculum thermopropionicum . Genes involved in propionate metabolism of these two strains show a strong similarity. However, main differences are found in genes involved in the electron acceptor metabolism.